La prise en compte des innovations en matière de mobilité dans la planification urbaine : le cas des Services de transports personnalisés (STP) - Élodie Castex; Séverine Frère; Annette Groux (Développement Durable et Territoires)
This paper presents a research on the capacity of planning to integrate new forms of mobily and innovation in transportation modes. From the examples of carpolling, carsharing (car clubs), bike-sharing and demand responsive systems, this paper tempt to understand how theses innovated transportation modes are considered in french public policy and especially in urban planning documents. The final aim is to improve the planning inscription of these news transportation modes in order to respond to spatial and environmental challenges and contribute to rethinking the planning.